Effect of Flocculation Technology on Lipids, Carbohydrates and Proteins and Extraction from Chlorella vulgaris (2018)
Nowadays, Chlorella vulgaris has emerged as an attractive source of metabolites such as lipids, proteins and carbohydrates, which are widely applied to obtain high value products. This work is focused on evaluating the effect of flocculation on metabolites recovery from Chlorella vulgaris microalgae biomass. Carbohydrates were extracted through acid and alkaline hydrolysis in order to identify the efficiency of these treatments for cell wall disruption. Protein quantification was carried out under alkaline conditions and lipids were recovered by solvent extraction with hexane. It was found that carbohydrate recovery was higher using centrifuged biomass (40.55%) than flocculated biomass (24.31%) by acid treatment, while alkaline treatment exhibited yield of 20.37% and 13.19%, respectively. In addition, efficiency of 53.75% and 32.27% in protein recovery was obtained from both centrifuged and flocculated biomass. The highest lipid extraction yield (54.2%) was achieved using acid hydrolysis and hexane solvent route when centrifuged biomass was used as metabolite source. These results suggested that flocculation affect significantly the efficiency of metabolites extraction.